Analisis Produk Pinjaman Pada Bank Wakaf Mikro Pondok Pesantren As’ad Kecamatan Danau Teluk Kota Jambi - Izzuddin, M. (Innovative: Journal Of Social Science Research, 2024)
This research aims to identify and analyze the Loan Products at the Micro Waqf Bank of Pondok Pesantren As'ad in the Danau Teluk Subdistrict, Jambi City. The study is conducted at the Micro Waqf Bank of Pondok Pesantren As'ad in Jambi City. The variable in this research is the implementation of loan products applied at the Micro Waqf Bank of Pondok Pesantren As'ad. The approach used in this research is a descriptive qualitative approach. The focus of this research is on how to manage the risk of customer default in the Micro Waqf Bank of Pondok Pesantren As'ad Jambi, using various methods, including the mudharabah method. This method is in line with the principles of Sharia economics, where the applied principles are cooperation, mutual assistance, and the principle of kinship. The findings of the assessment regarding the Analysis of Loan Products at the Micro Waqf Bank of Pondok Pesantren As'ad, Danau Teluk Subdistrict, Jambi City, indicate that the loan products implemented in the Micro Waqf Bank PP. As'ad Jambi is judged as qard hasan. The mudharabah method is one of the methods used. However, the existence of this method is not the main goal of establishing the Micro Waqf Bank; rather, it anticipates situations where customers fail to repay loans.